PENGEMBANGAN BUKU PERMAINAN TRADISIONAL DAN MOTOR COORDINATION - Ali, Masnur (Dharmas Education Journal (DE_Journal), 2023)
This research aims to produce a Traditional Game Book for Developing Coordination. With the development of this book, it will add references and become an alternative for learning and games that can be done in the home environment, school and on campus. This book aims to enable students to understand more fully about traditional games, be able to play traditional games with various biomotor skills and preserve traditional sports by playing games that can improve motor skills. This research is development research or Research & Development. The research data instruments consist of assessment instruments by validators (material, language and media), and media-based questionnaires based on research sample responses. The samples in this study were taken using a purposive sampling technique, taking into account the following conditions; 1) All students have taken Traditional Sports courses; 2) students are taught by the same lecturer. The overall results of this research data analysis show a figure of 75.37%. Therefore, it can be concluded that the completeness of the traditional game manual developed is at a level suitable for use as a learning medium.